All Days 2012
DOI: 10.2118/162673-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Vertical and Lateral Communication in an Unconventional Oil Reservoir Using Geochemistry and Reservoir Simulation

Abstract: Vertical and horizontal inter-well communication in unconventional reservoirs remains a major uncertainty. This paper presents the results of geochemical analyses performed on several wells in the Bakken and Three Forks unconventional oil reservoirs. Geochemical analyses performed on oil extracted from core, oil sampled while drilling, and oil produced after stimulation indicate that the geochemical signatures of the Bakken and Three Forks Formations are different and unique to its respective stratigraphic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This will give an insight into the vertical interference between layers as described by Rasdi et al (2012). Four wells are completed in Middle Bakken and another four are completed in Three Forks.…”
Section: Model 2: Heterogeneous Case -Thirty-stage Horizontal Wellsmentioning
confidence: 96%
See 2 more Smart Citations
“…This will give an insight into the vertical interference between layers as described by Rasdi et al (2012). Four wells are completed in Middle Bakken and another four are completed in Three Forks.…”
Section: Model 2: Heterogeneous Case -Thirty-stage Horizontal Wellsmentioning
confidence: 96%
“…The hydraulic fracture, micro-fracture, and matrix properties were obtained from production data analysis, detailed fracture characterization study, and core permeability measurements from the study area (Rasdi et al, 2012). In both models, the dual-porosity is a system where the flow path in the stimulated reservoir region begins with the nano-scale matrix flow to natural fractures to hydraulic fracture and to the wellbore.…”
Section: Simulation Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic proppant provides not only greater crush resistance but also allows for higher conductivity (Rankin et al 2010;Terracina et al 2010). Closure stress as determined during a DFIT was recommended to refine the proppant selection further and determine whether a different-strength proppant would be more appropriate.…”
Section: Pre-2009 South Antelope Field Completionsmentioning
confidence: 99%
“…1. Rasdi et al (2012) explores the vertical and lateral communication in the Bakken and found that the bounding layers can contribute to production with a superior completion method and or presence of through-going natural fractures. Connectivity between layers provides an opportunity to further investigate the correlation between observed field water cut and initial water saturation.…”
Section: Introductionmentioning
confidence: 99%